SISTEM INFORMASI INDUKSI GURU PEMULA BERBASIS WEB: Studi Kasus Yayasan Al-Musabbihin - Alfina, Ommi; Ummi, Khairul; Syahputri, Nita; Astuti, Ermayanti; Ikorasaki, Frans (Majalah Ilmiah METHODA, 2023)
The Beginner Teacher Induction Program is an introductory activity at a particular school/foundation, the training covers all teaching and learning activities and an introduction to the structure of the organization that exists in that institution, both the school and the foundation. The concept of work/method of work of the induction teacher includes 3 actors, namely the novice teacher as the object, the accompanying teacher as the provider of material directions and assignments to the novice teacher, and the Educational Institution as the control/validation of the results of learning/introduction to novice teachers. This research was built by applying a web base with the use of online media. The results of this study are in the form of a web-based application that can be used as an information tool to prepare novice teachers to become professional teachers in carrying out the learning process and as a reference in getting to know organizational schemes in a related agency.